2015
DOI: 10.1111/andr.12019
|View full text |Cite
|
Sign up to set email alerts
|

Congenital bilateral absence of the vas deferens: the impact of spermatogenesis quality on intracytoplasmic sperm injection outcomes in 108 men

Abstract: SUMMARYIn azoospermic men with congenital bilateral absence of the vas deferens (CBAVD), it is not known whether the outcomes of intracytoplasmic sperm injection (ICSI) depend on the quality of testicular spermatogenesis (as determined histopathologically). We retrospectively studied the impact of spermatogenesis quality on ICSI outcomes in 108 azoospermic men with CBAVD consulting in a university hospital's department of andrology and reproductive biology. As part of an ICSI program, sperm samples were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…Spermatozoa was obtained from all nine patients undergoing MESA or TESE surgeries, but most of these patients had weak sperm motility (mostly grade C or D) and a high sperm abnormality rate (97% to 100%; Table . Llabador et al evaluated sperm retrieval and ICSI outcomes of 108 men with CBAVD. Only 19.4% (21/108) had normal spermatogenesis, and 30.5% (33/108) had hypospermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa was obtained from all nine patients undergoing MESA or TESE surgeries, but most of these patients had weak sperm motility (mostly grade C or D) and a high sperm abnormality rate (97% to 100%; Table . Llabador et al evaluated sperm retrieval and ICSI outcomes of 108 men with CBAVD. Only 19.4% (21/108) had normal spermatogenesis, and 30.5% (33/108) had hypospermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on semen analysis of 4,822 men, Stone et al verified that daily sperm production significantly declines after 34 years of age (Stone et al, 2013). Hypospermatogenesis was histopathologically detected in 33/54 (61.1%) males with CBAVD that had been subjected to testicular sperm extraction (Llabador et al, 2015). By analyzing 85 CBAVD patients who had undergone PESA-ICSL, Elhanbly et al demonstrated that paternal age was negatively correlated with sperm count, motility, vitality, and normal sperm morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Among CFTR positive individuals, 46% have two mutations, and only 28% have a single mutation (Yu et al, 2012). Besides the CBAVD obstructive azoospermia effect, there is evidence for impaired spermatogenesis in individuals with CBAVD (Meng et al, 2001;Llabador et al, 2015). This is the first report of a person with Beare-Stevenson Syndrome whose father had CBAVD.…”
Section: Introductionmentioning
confidence: 85%
“…Преконцепционная профилактика муковисцидоза у пациентов и супружеских пар с муковисцидозом при планировании беременности должна включать медико-генетическое консультирование, так как у них повышен риск рождения ребенка с муковисцидозом [21][22][23]. Рекомендуется проведение анализа частых мутаций гена CFTR у супруга пациента с муковисци-дозом, а в случае выявления носительства патогенных вариантов гена CFTR -проведение преимплантаци-онной и/или пренатальной диагностики [8,21].…”
Section: Discussionunclassified